2005
DOI: 10.1158/1078-0432.ccr-04-2133
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the sFLT-1 Gene in Morris Hepatoma Results in Decreased Growth and Perfusion and Induction of Genes Associated with Stress Response

Abstract: Purpose: Inhibition of tumor angiogenesis is emerging as a promising target in the treatment of malignancies. Therefore, monitoring of antiangiogenic approaches with functional imaging and histomorphometrical analyses are desirable to evaluate the biological effects caused by this treatment modality.Experimental Design: Using a bicistronic retroviral vector for transfer of the soluble receptor for the vascular endothelial growth factor (sFLT) hepatoma (MH3924A) cell lines with sFLT expression were generated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…2 However, there is only indirect evidence for the role of sFlt-1 on endothelial cell apoptosis because the authors used sFlt-1 gene transfer in hepatoma and renal cell carcinoma models. 24,25 Herein, we proved this effect by using recombinant protein and showed that the proapoptotic effect was reversed by neutralization of sFLt-1. The proapoptotic activity found in patient serum and shown by recombinant sFlt-1 probably contributes to the antiangiogenic activity described above.…”
Section: Discussionmentioning
confidence: 86%
“…2 However, there is only indirect evidence for the role of sFlt-1 on endothelial cell apoptosis because the authors used sFlt-1 gene transfer in hepatoma and renal cell carcinoma models. 24,25 Herein, we proved this effect by using recombinant protein and showed that the proapoptotic effect was reversed by neutralization of sFLt-1. The proapoptotic activity found in patient serum and shown by recombinant sFlt-1 probably contributes to the antiangiogenic activity described above.…”
Section: Discussionmentioning
confidence: 86%
“…45 Briefly, the tumors were either paraffin-embedded or cryofixed in liquid nitrogen-cooled isopentane and stored at À80 1C before further processing. Then 6-mm sections were cut at À20 1C with a Microm Microtome, placed on Superfrost microscope slides (Fisher Scientific, Schwerte, Germany) and exposed to 4% paraformaldehyde.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…A previously described custom-developed computerassisted image analysis device 45 was used to quantify necrotic area of the paraffin-embedded, hematoxylineosin-stained tumor sections having the largest crosssectional diameter. The ratio of the necrotic area to the total tumor area was calculated and expressed as a percentage.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The human HPV16 immortalized keratinocyte cell line HPV16-GM (Dr. Pascal Tomakidi, University Hospital Heidelberg, Germany) was cultured in keratinocyte growth medium 2 with supplements (PromoCell). Human umbilical vein endothelial cells (HUVECs) were isolated as described in the literature (15). HUVEC cultivation was performed on gelatin (1%)-coated cell culture flasks using medium 199 (Invitrogen) containing 20% fetal calf serum, 2 mM glutamine, 100 IU/mL penicillin, 100 IU/mL streptomycin, and 2 ng bFGF/mL (Roche Diagnostics).…”
Section: Cell Linesmentioning
confidence: 99%